Comparing the Psychometric Properties of a Scale Across Three Likert and Three Alternative Formats: An Application to the Rosenberg Self-Esteem Scale. (August 2023) - Zhang, Xijuan; Zhou, Linnan; Savalei, Victoria
Zhang and Savalei proposed an alternative scale format to the Likert format, called the Expanded format. In this format, response options are presented in complete sentences, which can reduce acquiescence bias and method effects. The goal of the current study was to compare the psychometric properties of the Rosenberg Self-Esteem Scale (RSES) in the Expanded format and in two other alternative formats, relative to several versions of the traditional Likert format. We conducted two studies to compare the psychometric properties of the RSES across the different formats. We found that compared with the Likert format, the alternative formats tend to have a unidimensional factor structure, less response inconsistency, and comparable validity. In addition, we found that the Expanded format resulted in the best factor structure among the three alternative formats. Researchers should consider the Expanded format, especially when creating short psychological scales such as the RSES.